ANALYSIS OF USING BIOMETRIC AUTHENTICATION SYSTEM IN KATSINA STATE INSTITUTE OF TECHNOLOGY AND MANAGEMENT (KSTIM) LIBRARY - Sani, Maryam; Abba, Umar (FUDMA Journal of Sciences, 2025)
This research investigates the feasibility and benefits of implementing biometric authentication in the Katsina State Institute of Technology and Management (KSITM) Library, emphasizing its potential to enhance security and safeguard sensitive information. Traditional methods, like passwords and tokens, are vulnerable as they can be easily shared or compromised, often leading to security lapses. Biometrics, however, provide a more secure solution by using unique physical characteristics, such as fingerprints, hand geometry, palm veins, retina and iris patterns, facial recognition, signature, and voice analysis, to accurately verify individual identities. The study reviews these biometric methods, assessing their usability, advantages, and potential drawbacks. A questionnaire-based approach was used to gauge the satisfaction and receptiveness of KSITM’s staff and students toward biometric systems. Findings show that 85% of respondents consider biometric authentication an essential improvement for the library, demonstrating a strong preference for it over traditional methods. Respondents showed the highest preference for fingerprint recognition, favoring its balance of convenience, security, and reliability. This feedback suggests that implementing a biometric system could enhance the library’s security infrastructure and reduce the risks associated with traditional access methods. Overall, the positive response indicates that biometric authentication is both a viable and beneficial security measure for KSITM, fostering a more secure and controlled environment for students and staff.